2011
DOI: 10.1159/000323941
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency as a Strong Predictor of Asthma in Children

Abstract: Background: Epidemiological studies suggest a link between vitamin D deficiency in early life and development of asthma in later life. Aim: The aim of this study was to measure serum vitamin D levels in asthmatic children and to compare these to healthy non-asthmatic controls. Methods: Asthmatic (n = 483) and healthy control (n = 483) children were recruited from the Pediatric Allergy-Immunology Clinics of Hamad General Hospital and the Primary Health Care Clinics in Qatar from October 2009 to July 2010. All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
164
5
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(191 citation statements)
references
References 43 publications
12
164
5
10
Order By: Relevance
“…The severity of Vitamin D deficiency was found to be associated with severity of childhood asthma. Our finding are also in conformity with other studies which shows that insufficient vitamin D levels are associated with an increase in the risk of asthma exacerbations as found in patients of CAMP cohort and with augmented airway responsiveness and increased risk of asthma hospitalization in children with asthma (15,18) . One study also found an association between serum 25(OH)Vitamin-D levels and risk of an asthma related emergency department visit or hospitalization and concluded that vitamin D deficiency may be the strongest predictor of asthma, stronger than familial history of asthma or serum IgE levels [7] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The severity of Vitamin D deficiency was found to be associated with severity of childhood asthma. Our finding are also in conformity with other studies which shows that insufficient vitamin D levels are associated with an increase in the risk of asthma exacerbations as found in patients of CAMP cohort and with augmented airway responsiveness and increased risk of asthma hospitalization in children with asthma (15,18) . One study also found an association between serum 25(OH)Vitamin-D levels and risk of an asthma related emergency department visit or hospitalization and concluded that vitamin D deficiency may be the strongest predictor of asthma, stronger than familial history of asthma or serum IgE levels [7] .…”
Section: Discussionsupporting
confidence: 93%
“…Several epidemiological studies have reported about vitamin D deficiency and its association with an increased incidence of asthma and other allergy symptoms [6]. Some studies have found out vitamin D deficiency was the strongest predictor of asthma stronger than familial history of asthma or serum IgE levels and familial history of vitamin D deficiency also being a predictor of asthma [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D vitamininin %10'u gıdalar ile alınmakta %90'ı güneş ışı-ğındaki UV ile deride sentezlenmektedir (3). Günümüzde astım ve D vitamini eksikliği prevalansı oranlarının paralel olarak artmasından batı tipi yaşam tarzının benimsenmesi ile beslenme alışkanlıklarının değişmesi ve dış ortamda daha az vakit geçirilmesinin rol oynadığı düşünülmektedir (4). D vitamini etkisini biyolojik olarak aktif olan formu 1-25(OH)D 3 'ün (kalsitriol) vitamin D reseptörüne (VDR) bağlanması ile göstermektedir.…”
Section: Introductionunclassified
“…Bazı kesitsel çalışmalarda serum D vitamini düzeylerinin astımlı çocuklarda sağlıklı çocuklara göre daha düşük olduğu (4,(10)(11)(12) sınırlı sayıdaki çalışmada serum D vitamini düzeylerindeki yüksekliğinin astım riskinde artmaya neden olduğu gösterilmiştir (13,14). Bazı çalışmalarda ise bu farklılıklar gözlenmemiştir (15)(16)(17)(18)(19).…”
Section: Introductionunclassified